Diversifikasi Ampas Tahu Menjadi Olahan Mie Basah dengan Metode Quality Function Deployment (QFD) - Anggraini, Denny Astrie; St Nova Meirizha; Siregar, Parningotan (SURYA TEKNIKA, 2024)
Glycine Max is a by-product waste from the tofu-making process that has the potential to be utilized as an alternative raw material in the food industry. However, due to the limited knowledge from the community means that its utilization is not carried out optimally, so that it only provides very small economic benefits or, if disposed of directly, can cause environmental pollution. To pvercome these issues, the idea emerged to use Glycine Max as a diversification product in the form of economically valuable fresh noodles. This research is designed using the Quality Function Deployment (QFD) method. Sample collection is determined by convenience sampling, and the sample size is determined using a sample quota. The specifications for developing the diversified fresh noodle products include Glycine Max Flour, Wheat Flour, Eggs, and other raw materials. The selling price of the developed diversified fresh noodle product is Rp.13,000/ kilogram.